Contourite identification along Italian margins: The case of the Portofino drift (Ligurian Sea). (November 2017) - Cattaneo, Antonio; Miramontes, Elda; Samalens, Kevin; Garreau, Pierre; Caillaud, Matthieu; Marsset, Bruno; Corradi, Nicola; Migeon, Sébastien
Abstract: A brief review of the published evidence of current deposits around Italy is the occasion to test the robustness of matching bottom current velocity models and seafloor morphologies to identify contourite drifts not yet documented. We present the result of the regional hydrodynamic model MARS3D in the Northern Tyrrhenian and Ligurian Sea with horizontal resolution of 1.2 km and 60 levels with focus on bottom current: data are integrated over summer and winter 2013 as representative of low and high intensity current conditions. The Eastern Ligurian margin is impacted by the Levantine Intermediate Water (LIW) with modeled mean velocity of bottom current up to 20 cm s −1 in winter 2013 and calculated bottom shear stress exceeding 0.2 N m −2 in water depth of 400–800 m. By crossing this information with seafloor morphology and geometry of seismic reflections, we identify a sediment drift formerly overlooked at ca 1000 m water depth. The Portofino separated mounded drift has a maximum thickness of at least 150 m and occurs in an area of mean current velocity minimum. Independent evidence to support the interpretation include bottom current modelling, seafloor morphology, seismic reflection geometry and sediment core facies. The adjacent areas impacted by stronger bottom currents present features likely resulted from bottom current erosion such as a marine terrace and elongated pockmarks. Compared to former interpretation of seafloor morphology in the study area, our results have an impact on the assessment of marine geohazards: submarine landslides offshore Portofino are small in size and coexist with sediment erosion and preferential accumulation features (sediment drifts) originated by current-dominated sedimentary processes. Furthermore, our results propel a more general discussion about contourite identification in the Italian seas and possible implications. Graphical abstract: Highlights: Over the last ten years studies on contourites around Italy multiplied. The MARS3D circulation model shows a vein of LIW reaching the Ligurian margin. Superposing bottom current velocity and morphology helps identify contourites. The Portofino mounded drift in 1000 m w.d. is immediately downslope of the LIW. Evidence of erosion and mass wasting is present within and nearby the drift.